Predictors of Meningitis with First Febrile Seizure - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers in Delhi, India, investigated the prevalence of bacterial meningitis in 497 children aged 6-18 months admitted to hospital with a first seizure with fever.